A Novel Technique for Clock Synchronization to Increase Network Lifetime in WSN - Iqbaljeet,; Rana, Sonal (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor network has no central controller. Energy consumption is the major issue of wireless sensor network. In this paper, we have discussed routing protocol which utilized more energy. The energy must be quantized for computational purposes. Giving greater probability to nodes with higher energy, to be selected as CH, helps in better distribution of energy and more reliable message transmission. In this paper, diffusion based technique is used to synchronized cluster head clock. By doing so, energy consumption has been reduced in terms of energy, packet loss and delay.